“Finding meaning of work through a good action”: The mediation effect of meaning of work between perceived corporate social responsibility and organizational identification - Kim, ByungJik; Ji, WonKoo; Jeon, SangGil (Korean Journal of Industrial and Organizational Psychology, 2015)
This study tested whether meaning of work mediated the link between perceived corporate social responsibility and organizational identification. In order to examine the hypothetical model, 11843 employees were sampled across three time points. In structural equation modeling, the hypothetical model explaining the structural paths and the goodness of fit of the model were evaluated. The results showed that meaning of work mediated the relationship between perceived corporate social responsibility and organizational identification. The implications and limitations of the study as well as suggestions for future studies were discussed.